FOOD AND FEEDING OF THE POST-LARVAE AND JUVENILES OF MEGALOPS CYPRINOIDES (BROUSS.) - Noble, A (Indian Journal of Fisheries, 2011)
Post-larvae of Megalops cyprinoides collected from the inshore area offKarwar were reared ia the laboratory into juveniles. They were fed in the laboratorywith live plankton and their food and feeding were noted. They ate onlythe zooplankton and distinguished the edible from the non-edible, the big fromthe small and the live from the dead.